Descartes and the metaphysics of human nature - Skirry, Justin (Continuum studies in philosophy., 2005)
The traditional account of mind/body union attributed to Descartes supposes that the immaterial, thinking mind and the material, non-thinking body interact by means of efficient causation - that the mind causes events in the body, e.g. the voluntary raising of an arm, and vice versa, e.g. the visual sensation of a tree. But this gives rise to a notorious philosophical problem: how can this causal interaction occur between the spiritual mind and the physical body since they have absolutely nothing in common and cannot come into contact with one another?Justin Skirry's book shows how Descartes i.